A longitudinal study of virtual teamwork with and without group support systems. (31st August 2007) - Hung, Shin-Yuan; Dai, Chuan-I; Chang, Chia-Ming
This study compares the effectiveness of Group Support Systems (GSS) versus non-GSS tools in supporting virtual teamwork. Using a field experiment, the results show that non-GSS tools sometimes are not worse than GSS for virtual teamwork. Implications from these findings are also discussed.